2019
DOI: 10.1038/s41467-019-10954-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell type-dependent differential activation of ERK by oncogenic KRAS in colon cancer and intestinal epithelium

Abstract: Oncogenic mutations in KRAS or BRAF are frequent in colorectal cancer and activate the ERK kinase. Here, we find graded ERK phosphorylation correlating with cell differentiation in patient-derived colorectal cancer organoids with and without KRAS mutations. Using reporters, single cell transcriptomics and mass cytometry, we observe cell type-specific phosphorylation of ERK in response to transgenic KRAS G12V in mouse intestinal organoids, while transgenic BRAF V600E … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 70 publications
14
62
1
Order By: Relevance
“…However, recent studies have shown metastasis and stemness can be uncoupled in colorectal cancer metastasis 53 , and that oncogenic mutations and paracrine signals can reverse developmental trajectories so that more differentiated cells can regain stem cell characteristics [54][55][56] . Here, we show that a gradient of ERK target gene expression is associated with developmental latent time in CRC organoids, extending our previous finding of graded ERK activity in CRC organoids 57 . The results imply a capacity for intrinsic regulation of CRC cell lifetimes via MAPK.…”
Section: Mapk Target Gene Expression Defines Crc Differentiation Statessupporting
confidence: 89%
“…However, recent studies have shown metastasis and stemness can be uncoupled in colorectal cancer metastasis 53 , and that oncogenic mutations and paracrine signals can reverse developmental trajectories so that more differentiated cells can regain stem cell characteristics [54][55][56] . Here, we show that a gradient of ERK target gene expression is associated with developmental latent time in CRC organoids, extending our previous finding of graded ERK activity in CRC organoids 57 . The results imply a capacity for intrinsic regulation of CRC cell lifetimes via MAPK.…”
Section: Mapk Target Gene Expression Defines Crc Differentiation Statessupporting
confidence: 89%
“…These data contrast with observations that ectopic expression of RAS mutants does drive strong over-activation of ERK, as would be expected from simple amplification by RAF/MEK/ERK (Konishi et al, 2007;Park et al, 2006). These contradictory observations could arise for various reasons, including feedback in the RAS/ERK pathway (Courtois-Cox et al, 2006), oncogene-induced senescence (Sarkisian et al, 2007), additional mutations, or tissue-or cell type-specific effects (Brandt et al, 2019). However, these possibilities cannot be disentangled without first addressing a major technical limitation inherent in the immunoblots and kinase assays that have been used almost exclusively to date.…”
Section: Introductioncontrasting
confidence: 58%
“…Several alterations in signalling pathway activity were also common across conditions. TGFB1 treatment and spheroids were associated with higher levels of ERK activity, which have both been linked to stemness in epithelial 34 and carcinoma cells 35 . In EGF-free media, paracrine/autocrine signalling is established, maintaining ERK activity in stem cell populations of intestinal organoids 35 .…”
Section: Brca1 Loss Promotes Emt-independent Stemness In Mosementioning
confidence: 97%
“…TGFB1 treatment and spheroids were associated with higher levels of ERK activity, which have both been linked to stemness in epithelial 34 and carcinoma cells 35 . In EGF-free media, paracrine/autocrine signalling is established, maintaining ERK activity in stem cell populations of intestinal organoids 35 . While these mechanisms may contribute to stemness in OSE spheroids or those treated with TGFB1, increased ERK activity was not enhanced following Snail overexpression or Brca1 loss.…”
Section: Brca1 Loss Promotes Emt-independent Stemness In Mosementioning
confidence: 97%